IMPLEMENTASI PEMUNGUTAN RETRIBUSI PELAYANAN PASAR DI PASAR SIMPANG SARI PERSPEKTIF FIQH SIYASAH TANFIDZIYYAH - Aprilia, Reza; Frenki; Hermanto, Agus (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2025)
Retribution refers to the payment imposed for the provision of market service facilities carried out by the local government. Its implementation must be conducted properly and in accordance with statutory regulations to ensure optimal benefits for the community. However, in practice, the collection of retribution fees at Simpang Sari Market differs from the stipulations outlined in Article 18, Paragraph (2) of the Regent Regulation of West Lampung Regency, which states: “Retribution officers are prohibited from altering or increasing the amount of the retribution fee.” In reality, the amount of retribution collected by officers diverges from the officially prescribed tariff. This study aims to investigate and analyze the implementation of market service retribution collection at Simpang Sari Market, and to examine it from the perspective of Fiqh Siyasah Tanfidziyyah (the Islamic theory of administrative governance). The research adopts a field research methodology using a descriptive approach, with data gathered through interviews and direct observation. Data were collected from pre-selected informants to ensure accuracy and relevance for this study. Although the local government has established regulations and provided implementation guidelines for the collection of market service retribution, several issues have emerged in practice. These include a lack of understanding among market vendors regarding the retribution system, poor coordination among collection officers, and the involvement of unauthorized individuals who collect fees outside the formal governmental structure.